Role of heparanase in ARDS through autophagy and exosome pathway (review) - Feng, Fei; Wang, Lin-Jun; Li, Jian-Chun; Chen, Ting-Ting; Liu, Liping (Frontiers in Pharmacology, 2023)
Acute respiratory distress syndrome (ARDS) is the most common respiratory disease in ICU. Although there are many treatment and support methods, the mortality rate is still high. The main pathological feature of ARDS is the damage of pulmonary microvascular endothelium and alveolar epithelium caused by inflammatory reaction, which leads to coagulation system disorder and pulmonary fibrosis. Heparanase (HPA) plays an important role in inflammation, coagulation, fibrosis. It is reported that HPA degrades a large amount of HS in ARDS, leading to the damage of endothelial glycocalyx and the release of a large number of inflammatory factors. HPA can increase the release of exosomes through syndecan-syntenin-Alix pathway, leading to a series of pathological reactions; at the same time, HPA can cause abnormal expression of autophagy. Therefore, we speculate that HPA promotes the occurrence and development of ARDS through exosomes and autophagy, which leads to a large amount of release of inflammatory factors, coagulation disorder and pulmonary fibrosis. This article mainly describes the mechanism of HPA on ARDS.